2018
DOI: 10.3390/su10062087
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Environmental Awareness and Its Connection to Local Environmental Management in Water Conservation Zones: The Case of Beijing, China

Abstract: This paper aims at investigating the change over time in the environmental awareness in rural Chinese communities and its correlation with environmental management measures implemented at the local level. We identify three main components of awareness, namely: perception, behavior, and attitude toward environmental management measures. Data were collected from two surveys in three villages in northern China in 2006 and 2015 that interviewed 125 and 129 respondents, respectively, and were analyzed employing an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
36
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(52 citation statements)
references
References 54 publications
5
36
0
3
Order By: Relevance
“…Third, in addition to these external influences, domestic pressures have significantly increased in the past decade in China (Faria & Andersen, 2017; Lin, 2010; Yin & Zhang, 2012). Environmental problems, such as high air and water pollution, have caused a national rethinking among Chinese people and induced a call for more responsible social and environmental business practices (Du et al, 2018; Wang, Sun, Yang, & Yuan, 2016). Fourth, international buying firms sourcing from Chinese suppliers exert pressure on these firms to reduce the environmental and social impact of their products and processes through expected certifications and codes of conduct (Jiang, 2009; Schleper & Busse, 2013; Wu et al, 2016; Zhu, Sarkis, & Lai, 2012).…”
Section: Methodsmentioning
confidence: 99%
“…Third, in addition to these external influences, domestic pressures have significantly increased in the past decade in China (Faria & Andersen, 2017; Lin, 2010; Yin & Zhang, 2012). Environmental problems, such as high air and water pollution, have caused a national rethinking among Chinese people and induced a call for more responsible social and environmental business practices (Du et al, 2018; Wang, Sun, Yang, & Yuan, 2016). Fourth, international buying firms sourcing from Chinese suppliers exert pressure on these firms to reduce the environmental and social impact of their products and processes through expected certifications and codes of conduct (Jiang, 2009; Schleper & Busse, 2013; Wu et al, 2016; Zhu, Sarkis, & Lai, 2012).…”
Section: Methodsmentioning
confidence: 99%
“…Even so, environmental data still do not seem to have much impact on the outcome of these processes and are not always considered as much as they should be, as comments in our study clearly showed. Earlier research points out the need for communication and dialogue already early in the planning process, and that increased awareness and systematic use of environmental data is needed [3,4,6,13,20,21]. From our own research, suggestions on how to use environmental data highlighted the need for openness and accessibility, such as a common geodatabase, and low-resolution national data for local use.…”
Section: Kg 1 the Need For Increased Environmental Awareness And Sysmentioning
confidence: 90%
“…For instance, in many Swedish compact city centers, EU permitted levels of sound pollution are exceeded [19], and in order to densify the city, new limit values are needed for sound. Alongside densification policies, it is therefore important to create a certain degree of environmental awareness [20] and commitment from a wide range of stakeholders involved in environmental assessment and urban planning. With this objective, there is a growing general need for communication and dialogue [3][4][5] early in the planning process.…”
Section: The Need For Increased Environmental Awareness and Systematimentioning
confidence: 99%
“…For another, even if local leaders are committed to improving waste management, effective policy instruments are indispensable to bring out long-term change when public acceptance of waste sorting remains low. Public awareness of waste management issues in China remains inadequate [89,90]. A survey recently conducted in rural areas of China finds that only 23.9% of respondents knew waste classifications [91].…”
Section: Questionable Effectiveness Of Top-down Hsw Sorting Policy Inmentioning
confidence: 99%